2020
DOI: 10.1101/2020.11.04.368282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision medicine for the rescue of specific impairments in social behavior associated with the A350VIqsec2mutation

Abstract: In this study we tested the hypothesis that precision medicine guided therapy targeting glutamatergic neurotransmission could rescue behavioral deficits exhibited by mice carrying a specific mutation in the Iqsec2 gene. The IQSEC2 protein plays a key role in glutamatergic synapses and mutations in the IQSEC2 gene are a frequent cause of neurodevelopmental disorders. We have recently reported on the molecular pathophysiology of one such mutation A350V and demonstrated that this mutation downregulates AMPA type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The A350V mouse model was generated using CRISPR technology based on a human de novo mutation 32 and demonstrated a significant reduction in the surface expression of GluA2 AMPA receptors in hippocampal neurons along with increased locomotion activity and abnormal social behavior. Further, a more recent study that thoroughly characterized social behaviors in this model found that A350V mice display deficits in sex preference and emotional state preference behaviors 33 . Collectively, these findings demonstrate that the A350V mouse model manifests some of the abnormalities found in the human condition that inspired the generation of this mouse model.…”
Section: Introductionmentioning
confidence: 95%
“…The A350V mouse model was generated using CRISPR technology based on a human de novo mutation 32 and demonstrated a significant reduction in the surface expression of GluA2 AMPA receptors in hippocampal neurons along with increased locomotion activity and abnormal social behavior. Further, a more recent study that thoroughly characterized social behaviors in this model found that A350V mice display deficits in sex preference and emotional state preference behaviors 33 . Collectively, these findings demonstrate that the A350V mouse model manifests some of the abnormalities found in the human condition that inspired the generation of this mouse model.…”
Section: Introductionmentioning
confidence: 95%